2011
DOI: 10.1007/128_2011_214
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of Metalloproteins

Abstract: Metalloproteins represent a large share of the proteomes, with the intrinsic metal ions providing catalytic, regulatory, and structural roles critical to protein functions. Structural characterization of metalloproteins and identification of metal coordination features including numbers and types of ligands and metal-ligand geometry, and mapping the structural and dynamic changes upon metal binding are significant for understanding biological functions of metalloproteins. NMR spectroscopy has long been used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 182 publications
0
3
0
Order By: Relevance
“…Analyses of protein-metal complexes by NMR are always challenging because the position of complexation within the protein needs to be determined by other means, however their prevalence in nature requires their study and many excellent reviews have been written on the subject [24][25][26][27]. In cases of paramagnetic metal ions, the region around the iron is effectively erased from the NMR spectrum due to paramagnetic linebroadening from fast relaxation.…”
Section: Metal Binding In Biological Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of protein-metal complexes by NMR are always challenging because the position of complexation within the protein needs to be determined by other means, however their prevalence in nature requires their study and many excellent reviews have been written on the subject [24][25][26][27]. In cases of paramagnetic metal ions, the region around the iron is effectively erased from the NMR spectrum due to paramagnetic linebroadening from fast relaxation.…”
Section: Metal Binding In Biological Systemsmentioning
confidence: 99%
“…Chemical shift mapping is used to identify the binding site and is done by titrating the apo peptide with the metal ion and following perturbations in chemical shift and line-broadening in the NMR spectrum to determine the position of interaction of the ion on the peptide [27]. The coordination geometry of metal ions also requires experimental determination as the mode of binding and ligands can alter the bound structure [27].…”
Section: Use Of Nmr In the Study Of Peptide-metal Complexationmentioning
confidence: 99%
“…Metal ions play essential roles in maintaining the structure and function of metalloproteins. 11–16 The in-cell NMR technique has been successfully applied to investigate the interactions of proteins with metal ions, such as Zn 2+ , Cu 2+ , and Cd 2+ , in living cells by the Lucia Banci group, and their results suggested that interactions in living cells were different from those in vitro . 17–21 It has been theoretically predicted that intracellular macromolecular crowding can promote protein folding by 1–3 orders of magnitude and the cellular environment affects interactions between metal ions and proteins.…”
mentioning
confidence: 99%